Effect of lifestyle on blood pressure in Portuguese population under antihypertensive drugs. (13th November 2019) - Salvador, M R; Gonçalves, S C; Romana, G Q; Nunes, B; Kislaya, I; Dias, C M; Rodrigues, A P
Abstract: Background: Hypertension is one of the main risk factors for disability and death from cardiovascular diseases. Current guidelines include initiatives to control blood pressure values in hypertensive patients that focus on lifestyle changes. The main objective of this study was to estimate the association between lifestyle and blood pressure in patients under antihypertensive drugs. Methods: An analysis of the data of Portuguese Health Examination Survey (INSEF) was performed. Individuals who met INSEF inclusion criteria and who referred to be under antihypertensive drugs in the two weeks prior to the questionnaire were studied. Lifestyle variables (alcohol consumption, smoking, additional salt intake, fruit and vegetables consumption, practice of physical activity) were measured by questionnaire, and blood pressure values were obtained by physical examination. Associations between lifestyle factors and blood pressure, stratified by sex and adjusted to sociodemographic variables and to obesity, were estimated through a multiple linear regression model. Results: Alcohol consumption (ß=6.31, p = 0.007) and smoking (ß=4.72, p = 0.018) were associated with systolic blood pressure in men. Additional salt intake, fruit and vegetable consumption, and practice of physical activity were not associated with blood pressure in men. In women, no association was observed for any behavioural variable. Conclusions: These conclusions reinforce the need, also in the population under antihypertensive drugs, particularly in the male sex, to focus the fight against high systolic blood pressure in these two modifiable and preventable behaviours: smoking and alcoholic consumption. Key messages: Alcohol consumption and smoking are the behavioral determinants associated with high systolic blood pressure values in men under antihypertensive drugs. These conclusions reinforce the need to focus the fight against high systolic blood pressure in the preventable and modifiable behavioural determinants.